Lameness prevalence in lactating and dry cows – expert's, student's and farmers' assessments - Laschinger, Jasmin; Linnenkohl, Sophie; Fuerst-Waltl, Birgit; Kofler, Johann (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
Objective The aim of this study was to evaluate differences in lameness prevalence among Austrian dairy farms for both lactating and dry cows as assessed by locomotion scoring (LCS 1–5) by an expert and a student who had received brief training in locomotion scoring and by farmers’ estimates and by farmers’ lameness assessments.Materials and methods In total, 632 cows from 11 farms were evaluated, including 553 lactating and 79 dry cows. Lameness prevalence was calculated for all farms collectively as well as for individual farms. The ratio of lameness prevalence determined by the student/expert (Student’s Assessment Index: SAI), the ratio between farmers’ assessments/expert assessments (Farmers’ Assessment Index: FAI) and the ratio between farmers’ estimates/expert assessments (Farmers’ Detection Index: FDI) were calculated.Results For the expert, the mean lameness prevalence (LCS≥2) among all 632 cows was 63.1%, while for the student it was 60.2%, and the farmers’ assessment was 37.3%, resulting in a mean difference of 25.8% between the expert and the farmers. In cows with LCS 2, the SAI was 99.6%, in cows with LCS 3, it was 84.4%, and in cows with LCS≥4, it was 88.6%. The mean FDI and FAI for all cows on the 11 farms were 35.1% and 58.2%, respectively, with wide variation across farms (6.8–79.1% and 17.8–94.7%, respectively). Overall, lactating and dry cows exhibited a high mean lameness prevalence (63.9% vs. 59.6%), which differed by only 4.3%.Conclusions and clinical relevance Farmers should actively assess their cattle for lameness on a regular basis. Moreover, they should be trained to identify lame cows (lactating and dry cows), especially those showing mild lameness (LCS 2). Since the recently trained student achieved similar high recognition rates as the expert, it is assumed that a training in locomotion scoring can contribute to higher recognition rates.
Keywords: Lameness prevalence; Student’s Assessment Index; Farmersʼ Assessment Index; Farmers’ Detection Index; cattle